Ethical Leadership and Employee Innovative Work Behavior: The Role of Thriving at Work as a Mediation Variable - Supriandi; Adi Rahmat; Adolf Bastian (SAINS ORGANISASI, 2022)
The purpose of this study was to determine the effect of ethical leadership on innovative work behavior of employees with thriving at work as a mediating variable. The population is the State Civil Apparatus of Indragiri Hilir Regency with a sample of 130 people. Data collection techniques using questionnaires and distribution using Google Sheets. Technical analysis of the data in this study is Structural Equation Modeling (SEM) using WarpPLS 7.0 for data processing. The findings of this study are that ethical leadership has an impact on the innovative work behaviour of ASN in the Indragiri Hilir Regency government. Ethical leadership affects the thriving at work of ASN in the Indragiri Hilir Regency Government. Thriving at work has an effect on the innovative work behavior of ASN in the Indragiri Hilir Regency Government. Ethical leadership affects the innovative work behavior of ASN in the Indragiri Hilir Regency Government through thriving at work.